2011
DOI: 10.1186/1423-0127-18-64
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan attenuated the higher vulnerability to inflammatory thermal hyperalgesia caused by prenatal morphine exposure in rat offspring

Abstract: BackgroundCo-administration of dextromethorphan (DM) with morphine during pregnancy and throughout lactation has been found to reduce morphine physical dependence and tolerance in rat offspring. No evidence was presented, however, for the effect of DM co-administered with morphine during pregnancy on inflammatory hyperalgesia in morphine-exposed offspring. Therefore, we attempt to investigate the possible effect of prenatal morphine exposure on the vulnerability to hyperalgesia and the possible therapeutic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The goal of this study is to evaluate the effects of co-administration of DM with methadone in the prenatal stage on offspring [ 21 , 29 , 31 ]. The doses we used are within the clinical therapeutic ranges converted to rats based on the body surface area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this study is to evaluate the effects of co-administration of DM with methadone in the prenatal stage on offspring [ 21 , 29 , 31 ]. The doses we used are within the clinical therapeutic ranges converted to rats based on the body surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DM reduced morphine reward as measured by CPP test, and this might be related to DM’s antagonizing effect on NMDA receptors that are involved in the activation of mesocorticolimbic dopaminergic systems [ 25 , 26 ]. Our previous studies also demonstrated that co-administration of DM with morphine during pregnancy and throughout lactation reduced several morphine-induced adverse effects [ 27 , 28 ] and could prevent higher vulnerability to inflammatory thermal hyperalgesia in rat offspring [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments with platelet derived growth factor (PDGF) ameliorated morphine-induced ROS productions and restored spine densities ( Cai et al, 2016 ). Furthermore, dextromethorphan, an active ingredient found in cough syrup, may be repurposed as a mitigator of adverse opioid effects during gestation and lactation periods since co-administration of dextromethophen with morphine were found to significantly attenuate morphine-induced neurologic effects ( Tao et al, 2011 ; Yang et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tempel et al [20] described that prenatal exposure to morphine, at doses of 75 mg on gestation day (GD) 16, induces tolerance responses to analgesic effects in rats, through the downregulation of opioid receptors. In contrast, Tao et al [13] postulated that intrauterine morphine administration at a dose of 2 mg/kg alters pain threshold, inducing hyperalgesia, mainly in female rats.…”
Section: Introductionmentioning
confidence: 93%
“…Besides, the newborn can undergo neonatal abstinence syndrome (NAS) in the first days after birth. Characterized by negative symptoms related to the central nervous system (CNS), as well as respiratory and digestive systems dysfunction, it was observed in NAS sneezing, lacrimation, impaired sucking, reduced sleep duration, and irritability, which leads to physiological stress, requiring intensive care service, as well as contributing to low weight birth [8,12,13].…”
Section: Introductionmentioning
confidence: 99%